2013
DOI: 10.1093/carcin/bgt365
|View full text |Cite
|
Sign up to set email alerts
|

[6]-Shogaol inhibits growth and induces apoptosis of non-small cell lung cancer cells by directly regulating Akt1/2

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer mortality worldwide. Despite progress in developing chemotherapeutics for the treatment of NSCLC, primary and secondary resistance limits therapeutic success. NSCLC cells exhibit multiple mutations in the epidermal growth factor receptor (EGFR), which cause aberrant activation of diverse cell signaling pathways. Therefore, suppression of the inappropriate amplification of EGFR downstream signaling cascades is considered to be a rational therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…Given that 6-SHO effectively inhibited the growth of prostate cancer cells regardless of STAT3 expression or activity, multiple mechanisms are likely involved in its effects on prostate cancer cell survival, including effects on STAT3, NF-kB, and possibly other signaling pathways. In this regard, it has been reported that 6-SHO induces apoptosis by generation of reactive oxygen species in human colorectal cancer cells, by directly regulating Akt1/2 in nonsmall cell lung carcinoma cells and by modulation of estrogen receptor stress in hepatocellular carcinoma cells (23,32,43). In addition, as shown in Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Given that 6-SHO effectively inhibited the growth of prostate cancer cells regardless of STAT3 expression or activity, multiple mechanisms are likely involved in its effects on prostate cancer cell survival, including effects on STAT3, NF-kB, and possibly other signaling pathways. In this regard, it has been reported that 6-SHO induces apoptosis by generation of reactive oxygen species in human colorectal cancer cells, by directly regulating Akt1/2 in nonsmall cell lung carcinoma cells and by modulation of estrogen receptor stress in hepatocellular carcinoma cells (23,32,43). In addition, as shown in Fig.…”
Section: Discussionmentioning
confidence: 85%
“…In colon and breast cancer cell lines, apoptosis has been reported after treatment with 10‐ΌM 6‐shogaol (Tan et al, ). Induction of apoptosis was further proven in prostate cancer (Saha et al, ), lung cancer (Kim et al, ), leukemia (Liu, Peng, Zhou, et al, ), and hepatocellular carcinoma (Hu, Zhou, Peng, et al, ) cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…Shogaol suppresses the proliferation of NSCLC cells by inducing cycle arrest (G1 and G2/M) and apoptosis [44]. Despite being more common and spreading more slowly than SCLC, most of NSCLC are diagnosed only when the cancer has metastasized; also, primary and secondary resistance limits therapeutic success.…”
Section: Other Dietary Sources In Chemoprevention Of Lung Cancermentioning
confidence: 99%
“…Despite being more common and spreading more slowly than SCLC, most of NSCLC are diagnosed only when the cancer has metastasized; also, primary and secondary resistance limits therapeutic success. Adopting appropriate preventing strategies might reduce the incidence and mortality from NSCLC [44].…”
Section: Other Dietary Sources In Chemoprevention Of Lung Cancermentioning
confidence: 99%